The associations of ferritin, serum lipid and plasma glucose levels across pregnancy in women with gestational diabetes mellitus and newborn birth weight - Jing Ji; Pei Wu; Guohua Li; Zhangya He; Shanshan Wang; Wenlu Yu; Chao Li; Yang Mi; Xiaoqin Luo (BMC, 2023)
Abstract Background Women with gestational diabetes mellitus (GDM) are at greater risk of abnormal birth weight. Since the level of biochemical indicators could often affect the intrauterine growth and development of the fetus, it is of great practical significance to understand the changes of biochemical levels across pregnancy in women with GDM and to find out the indicators that play an important role in predicting birth weight. Methods The data source of this study was from the Xi'an Longitudinal Mother-Child Cohort study (XAMC), in which women with GDM with normal and high pre-pregnancy body mass index (BMI) and their newborns between January 1st and March 31st in 2018 were included. The data of ferritin, serum lipid profile and fasting plasma glucose (FPG) of mothers in the three trimesters of pregnancy, as well as birth weight of newborns were all collected from medical records. Multiple linear regression and multivariate logistic regression analyses were used to explore the association of the biochemical indexes and birth weight. A P value < 0.05 was considered statistically significant. Results A total of 782 mother-infant pairs were finally included and divided into normal weight group (NG) (n = 530, 67.8%) and overweight/obesity group (OG) (n = 252, 32.2%) according to maternal pre-pregnancy BMI. The level of ferritin in both NG and OG decreased during pregnancy (P for trend < 0.001 for all), whereas the levels of total cholesterol (TC), high density cholesterol (HDL-C), low density cholesterol (LDL-C) and triglycerides (TG) all showed an upward trend (P for trend < 0.05 for all). The levels of FPG in the two groups remained in a relatively stable during the whole pregnancy even though it was higher in OG during the 2nd and 3rd trimesters, whilst HbAlc levels in NG women increased (P for trend = 0.043) during pregnancy. Meanwhile, the risk of macrosomia and large-for-gestational-age (LGA) increased with the increase of FPG level (P for trend < 0.05). Multivariate logistic regression analyses results showed that only FPG level in the 3rd trimester was correlated with birth weight, with birth weight increased by 44.9 g for each SD increase in FPG level. Conclusion Maternal FPG in the 3rd trimester is an independent predictor of newborn birth weight, and a higher level of that is associated with an increased risk of macrosomia and LGA.